2020
DOI: 10.3389/fimmu.2020.02068
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Galactose-Deficient IgA1 Derived From the Tonsils and Recurrence of IgA Nephropathy in Patients Who Underwent Kidney Transplantation

Abstract: Background: Recurrence of IgA nephropathy (IgAN) in the transplanted kidney is associated with graft survival, but no specific treatment is available. Tonsillectomy (TE) reportedly arrests the progression of IgAN in the native kidney. Thus, we conducted a single-center retrospective cohort study to evaluate the effect of TE prior to IgAN recurrence. Methods: Of the 36 patients with biopsy-proven IgAN who underwent kidney transplantation, 27 were included in this study. Nine patients underwent TE at 1 year afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Treatment of patients with IgAN has included several approaches that reduce circulating levels of Gd-IgA1. Tonsillectomy has been widely accepted in Japan [ 86 , 87 , 88 , 89 , 90 ]. Gd-IgA1 production by IgA1-secreting cells in tonsils is related to abnormalities in the expression of glycosyltransferase genes associated with core 1 O -glycosylation [ 91 ].…”
Section: Galactose-deficient Iga1 (Hit #1)mentioning
confidence: 99%
“…Treatment of patients with IgAN has included several approaches that reduce circulating levels of Gd-IgA1. Tonsillectomy has been widely accepted in Japan [ 86 , 87 , 88 , 89 , 90 ]. Gd-IgA1 production by IgA1-secreting cells in tonsils is related to abnormalities in the expression of glycosyltransferase genes associated with core 1 O -glycosylation [ 91 ].…”
Section: Galactose-deficient Iga1 (Hit #1)mentioning
confidence: 99%
“…It has also been reported that, in patients with IgAN, the T-cell area in the tonsils is significantly expanded and the ratio of IgA/IgG-producing cells is high compared with that in patients with chronic tonsillitis. Furthermore, tonsillectomy performed at 1 year after kidney transplantation significantly decreased the level of serum Gd-IgA1 and the recurrence rate of histological IgAN after kidney transplantation [ 70 ]. On the bases of these findings, serum Gd-IgA1 derived from the tonsillar B cells likely plays an important role in the pathogenesis of IgAN.…”
Section: Nasal-associated Lymphoid Tissue (Nalt)mentioning
confidence: 99%
“…Several studies suggest strategies as a part of prophylaxis to suppress IgAN recurrence, although no established induction therapy exists. As a prevention of IgAN recurrence, the Jikei group adopted elective tonsillectomy 1 year after renal transplantation and examined the relationship between tonsillectomy and serum GdIgA1 and GdIgA1 deposition in tonsils and kidneys [63]. They revealed that elective tonsillectomy reduced the rates of IgAN recurrence, coupled with decreased immunoreactivities of GdIgA1.…”
Section: Iga Nephropathymentioning
confidence: 99%
“…Next, our concern is therapeutic modalities available in IgAN recurrence. Although there is no specific guideline for renal transplant recipients, many institutions basically follow native IgAN treatments consisting of steroid pulse [65], rituximab, tonsillectomy [63], and elimination of other exacerbating factors. A simple observation strategy often takes place for many PR cases, especially in elderly recipients, combined with lifestyle guidance.…”
Section: Iga Nephropathymentioning
confidence: 99%